THE CONCEPT AND LEGAL FUNDAMENTALS OF DERIVATIVES (FINANCIAL INSTRUMENTS) IN THE REPUBLIC OF UZBEKISTAN - DILSHOD, KHABIROV (International Journal of Psychosocial Rehabilitation, 2020)
The paper concentrates on the legal analysis of approaches to the understanding of derivative financial instruments (derivatives). The author has analyzed laws and regulations governing relations in the derivatives market in the Republic of Uzbekistan and special features of their legal regulation in various legal systems. The author considers the processes of historical evolution and formation of the concept of derivative financial instruments (derivatives). Alongside this, the paper proposes findings of the special features of integrating new types of derivative financial instruments (derivatives) into the financial market of the Republic of Uzbekistan, as well as conclusions on the prospects and trends of sustainable formation of legal regulation of derivative financial instruments.In his research, the author proceeds from economic and sociocultural approaches to law and state. The matter of the paper demonstrates the permissible limits of independence of the financial market of the Republic of Uzbekistan. Obviously, despite the ongoing processes of globalization of the country’s economy accompanied by converging the national legal systems and harmonization of law in the field of financial legal standards, the tasks associated with this changes remain unresolved.As such tasks, the author considers bringing approaches to understanding terms related to the financial market and, in particular, the concept of ‘a derivative financial instrument (derivative)’ to authenticity. In doing this, the author draws attention to the importance of maintaining the traditional practice, local specifics and established customs in certain areas of legal regulation of this financial marketin the process of unifying and harmonizing the legislation.